Comprehensive lncRNA and mRNA profiles in peripheral blood mononuclear cells derived from ankylosing spondylitis patients by RNA-sequencing analysis. Issue 4 (28th January 2022) - Li, Chuangxin; Qu, Wa; Yang, Xuefeng
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The present study aimed to investigate the comprehensive expression profiles of long non-coding RNA (lncRNA) in ankylosing spondylitis (AS). The peripheral blood samples were collected from 6 AS patients and 6 age- and gender-matched healthy controls (HCs), and separated for peripheral blood mononuclear cells, followed by RNA-sequencing. Further bioinformatics analyses were performed to explore the significantly enriched biological processes, signaling pathways of differentially expressed lncRNAs (DElncRNAs) (based on cis-target and trans-target genes) and differentially expressed mRNAs (DEmRNAs). Principal component analysis plots indicated that both lncRNA and mRNA expression profiles could distinguish AS patients from HCs; heatmap diagram exhibited a relatively good consistency and tendency of lncRNA and mRNA expression profiles in AS patients and HCs, respectively; volcano plots exhibited 114 upregulated and 45 downregulated DElncRNAs, 284 upregulated and 435 downregulated DEmRNAs in AS patients compared with HCs; Gene ontology enrichment analyses indicated that DElncRNAs (based on cis-target and trans-target genes) and DEmRNAs were enriched in molecular functions (including DNA binding, protein binding, etc) and biological process (including immune response, inflammatory response, etc); Kyoto Encyclopedia of Genes and Genomes enrichment analyses revealed that these DElncRNAs (based on cis-target and trans-target genes) and DEmRNAs were enriched in immune and inflammation-related signaling, such as B cell receptor signaling pathway, TNF signaling pathway, NF-kappa B signaling pathway, etc. Our study displays the comprehensive expression profiles and functions of lncRNAs involved in AS, which provides reference for further researches discovering candidate lncRNAs with value in assisting early AS diagnosis.